(untitled) (Fiep Bulletin - online, 2011)
gle_mgufpa@yahoo.com.br The present study it had as objective to evaluate the dietary ingestion and body composition of dancers of the UFPA. Six pupils of choreographic dance of the School of Dance of the UFPA had been accompanied by currently. The collection of data was carried through at three distinct moments during a period of five months by means of a questionnaire of physical evaluation in which if anthropometrics information had registered (weight, cutaneous stature, folds and circumference of the waist) and a questionnaire of frequency of alimentary consumption to identify the alimentary habit of the dancers and to elaborate the dietary intervention after the first evaluation. For the analysis of the anthropometrics data comparisons between first and the second evaluation had been established, period without dietary intervention and between second and third, period with dietary intervention. It was observed that the total corporeal weight increased of the first one for the second evaluation of 52,9 +2,2 for 54,7 +4,7 kg and of this for third diminished for 53,2 +3,2 kg; the fat percentage increased of the first evaluation for second of 19,2 +4,0 for 22,8 + 2.4% and of this for the third evaluation with 23,5 + 3.6%; the lean weight diminished of the first evaluation for second of 42,7 +3,0 for 42,2 +3,9 kg and of this for the third evaluation with 40,7 +2,2 kg The BMI were inside of the band of normality in the three evaluations same with its increase of the first one for the second evaluation of 20,5 +1,0 for 21,2 +1,6 Kg/m ² and its reduction of this evaluation for third with BMI of 20,7 +1,6 Kg/m ². The circumference of the waist increased of the first one for the second evaluation of 68,3 +4,6 for 68,6 +5,2 cm and of this for the third evaluation it diminished for 68,5 +3,9 cm. This study it evidenced that the dietary intervention before did not have significant difference in the changes of the corporal compositions of the dancers after.